Confronting the corrupt - Hoffman, Paul, 1950 October 13- (Cape Town, South Africa : Tafelberg, 2016)
"The infamous Seriti Commission into the arms deal. The Glenister case following the disbanding of the Scorpions. Busting open the bread manufacturers' cartel. High drama; high stakes brought to South Africa courtesy of the Accountability Now NGO and its founder, Paul Hoffman. Join him in his journey from jaded silk to corruption buster - a fly-on-the-wall account of courtroom clashes, influential personalities, secrets and lies in the battle to speak truth to power. Confronting the Corrupt tells of Accountability Now's biggest battles, leading to landmark decisions in jurisprudence and earning its place in the small but determined group of organisations protecting and upholding the rule of law in SA."--Publisher description.
The early days -- To commission a commission -- The arms deal goes to Braamfontein -- The president throws in the towel -- The Seriti whitewash -- Polokwane, the Scorpions, and Glenister I -- Glenister II, and a meeting under the Flying Arch -- Stirring the pot after Glenister II -- The Constitutional Court drafts legislation -- Breaking the bread cartel -- The bread cartel goes to Bloemfontein... and Braamfontein -- Dealing with National Commissioners of Police -- Firepool or Waterloo? Accountability Now and Nkandla -- Epilogue: The idea is right, its time is now.
Includes index.
Keywords: Corruption -- South Africa; Corruption -- South Africa -- Prevention; Government accountability -- South Africa